Mapping Digital-Era Indonesian Character: A Bibliometric Analysis of Research on National Identity, Technology, and Future Governance (2020–2025) - Ali Anhar; Aghnia; Abid Nurhuda; Walid In'am Ahmad; Hamdi (WISE Pendidikan Indonesia, 2026)
This study maps research on Indonesian character in the digital era to clarify how national identity, technology, and future governance are connected in the literature. A bibliometric design was applied to Crossref metadata retrieved through Publish or Perish. From 1,000 records published between 2020 and 2025, 402 records met the predefined relevance and metadata criteria. Annual production, document sources, leading contributors, and term co-occurrence were analysed in VOSviewer 1.6.20. Publication output increased from 65 records in 2020 to a peak of 85 in 2023, before declining to 37 in 2025. Scientific journals accounted for 49.3% of the corpus. Term mapping retained 104 terms and identified four connected clusters: moral and personal formation, civic-pedagogical capacity, rights and institutions, and development and welfare. The least dense areas concerned democratic institutions, welfare, human development, health, and regional inequality. The study’s contribution is a future-governance interpretation of character research: digital citizenship, ethical AI use, and human-centred public innovation should be studied as integral, rather than peripheral, dimensions of Indonesian character.